ANALISIS SENSITIVITAS PARAMETER HYDRAULIC FRACTURING TERHADAP RECOVERY FACTOR PADA RESERVOIR TIGHT GAS - Agustiansyah Putra, Maulana
As time goes by, the increase of energy demands throughtout the world leads to the development of unconventional hydrocarbon. Tight gas is one of the unconventional hydrocarbon resources considered due it has huge gas potential. Tight gas is a reservoir with low permeability value, so it can not produce gas economically. Hydraulic fracturing stimulation and horizontal or multilateral wells is required to increase the flow rate and recovery factor. The objective of this study is to know the effect of hydraulic fracturing parameters to the recovery factor at gas plateau rate. This study also presents the correlation of the related hydraulic fracture parameters to recovery factor and gas plateau rate. The hydraulic fracturing parameters which tested in this study are number of wells, number of fractures, half-length fracture, and dimensionless fracture conductivity. The reservoir model data is obtained from literature and simulated using petroleum software. Reservoir simulation is performed to determine the value of recovery factor by inputting the hydraulic fracturing parameters in some cases. Obtained recovery factor then is being analysed to observe the effect of each inputted parameters to recovery factor. From the analysis, the most influencing parameter is, respectively, number of wells, number of fractures, half-length fracture, and dimensionless fracture conductivity. Empirical equation of the related hydraulic fracture parameters to recovery factor has R-squared value of 99.61%. In addition, also obtained empirical equations of the gas plateau rate with R-squared values of 99.6%. Further studies need to performed by adding economic variables to determine the most optimal design of hydraulic fracturing.